(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe knowledge, attitudes and practices in nutritional care for patients of nurses and related factors at National Lung Hospital in 2019. Methods: The cross - sectional study, through direct interviews with 213 nurses in 13 clinical departments. Results: 57.7% of nurses have good knowledge, 78.4% of nurses have positive attitude and 62.9% of nurses have good practice in nutritional care for patients. There is a statistically significant relationship between educational level, training, supervision, knowledge, attitude and help of colleagues with nutritional care practice of nurses (p<0.05). Conclusion: The nurses lack knowledge and practical skills on nutritional care for patients. There is a statistically significant relationship between training, supervision, knowledge, attitude and help of colleagues with nutritional care practice of nurses (p<0.05). This result will provide more evidences for the managers to have appropriate plans and solutions to improve the knowledge and practice of nutritional care for nurses, there by improving the quality of care and making the patients satisfied.